The effect of period of time (T) from 900Hz – 1820Hz of transcutaneous electrical nerve stimulator for biomedical application - A. Miskon,; M. S. Salleh,; S. N. M. Tawil,; Mohd Salman Mohd Sabri,; N. R. S. Rokmanuddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Transcutaneous Electrical Nerve Stimulator (TENS) is a device that can stimulate the nerves by using electric current. The main role of TENS is as a pain relief to users by replacing the usage of analgesic or drug. 2-Channel Defence Transcutaneous Electrical Stem Stimulator (2-Channel DTES) device and 5-Channel Defence Transcutaneous Electrical Stem Stimulator (5-Channel DTES) has been developed to improve the previous TENS devices but there were some shortcomings of the devices such as incoming noise in circuit as well as different measurement results if compared to simulation and experimental test. These problems may be solved by designing an alternative circuit of TENS to overcome the noise issue appearing during testing in which this study has tested and analyzed the basic circuit of TENS unit. Even though an issue of incoming small amount of generated electric current, apparently it would not affect the patient by using TENS. The capability of TENS as pain relief has been demonstrated to be comfortable, user friendly, and highly efficient to the user. From the experimental, it has been observed that the percentage measured for period of time, T from 900 Hz to 1820 Hz output measurement using implementation without electrode pads and with electrode pads of Transcutaneous Electrical Nerve Stimulator for biomedical application is around ± 5%.